The Influence of Comic Media Education “SIMEBA” (Siap Menghadapi Banjir) on the Self-Efficacy Level of Flood Disaster Preparedness Among Mts Muhammadiyah Sirau Students in 2023 - Septian Reza Perdana; M Hanif Prasetya Adhi (UM Purwokerto Press, 2024)
Background: Floods cause various kinds of losses in the form of property losses and social losses. Floods in Sirau Village routinely occur every year because of the village's geographical location which is concave, but the community is always not ready to make any preparations if a flood occurs, such as planning evacuation locations, carrying out evacuation simulation exercises, not preparing a first aid box or preparing a special place to store archives. important. People need to have good self-efficacy and knowledge to overcome problems in order to avoid their impacts. Method: This research used a pre-experimental design with one group pretest-posttest. The sample was 46 respondents using proportional random sampling technique. Then the Wilcoxon test is used for statistical tests. This research instrument uses a questionnaire to collect data, and comic media as an educational intervention. Results: This research shows that the majority of respondents received a good category after the intervention with a Self Efficacy level of 73.9%. The p value obtained from the Wilcoxon test is 0.00 < 0.05. This means that there is a significant influence on the level of self-ability on preparedness for flood disasters. Conclusion: Good Self Efficacy will influence the Respondent's abilities and skills in managing or dealing with uncontrollable situations such as disasters.